Personalized Nutrition - Biesiekierski, Jessica (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
"Personalised Nutrition" represents any initiative that attempts to provide tailor-made healthy eating advice based on the nutritional needs of each individual, as these are dictated by the individual's behaviour, phenotype and/or genotype, and their interactions. This Special Issue of Nutrients is dedicated to the development, implementation and assessment of the effectiveness of evidence-based "Personalised Nutrition" strategies. In this regard, a selection of reviews and original research manuscripts will bring together the latest evidence on how lifestyle habits, physiology, nutraceuticals, gut microbiome and genetics can be integrated into nutritional solutions, specific to the needs of each individual, for maintaining health and preventing diseases.